Ceramah Monolog tentang “Keselamatan oleh Anugerah, Bukan oleh Perbuatan” Berdasarkan Efesus 2:1–10 di Gereja Kristus Bojong Indah - Amirrudin Zalukhu (Universitas 45 Surabaya, 2025)
This Community Service Program was conducted at Gereja Kristus Bojong Indah on Sunday, October 6, 2024, in the form of a monologue lecture titled “A Gift, Not an Achievement,” based on Ephesians 2:1–10. The primary aim of this program was to reaffirm the gospel-centered understanding of salvation as a gift of God’s grace, not the result of human effort or works. Through an in-depth exposition of humanity’s spiritually dead condition (Ephesians 2:1–3), God’s initiative in salvation through Christ (Ephesians 2:4–7), and the affirmation that salvation is a divine gift (Ephesians 2:8–10), participants were invited to reflect on their lives as a response to God’s grace. The response from the congregation was notably positive, as seen in their engagement during post-service discussions and affirming feedback from church elders. This program contributed to the development of sound theological understanding and opened opportunities for further educational ministry through reflective lecture methods in local church settings.